A New ECG Steganography Based on Enhanced Coefficient Adjustment Technique and Least Significant Bit Substitution - Ching-Yu, Yang; Tsung-Hsiang, Hsu; Pei-Yun, Chen (Transactions on Engineering and Computing Sciences, 2023)
A new data hiding technique was presented to conceal the privacy of patient’s diagnosis and personal sensitive information in an electrocardiogram (ECG) signal. Instead of hiding one data bit in a host block at a time by traditional coefficient adjustment technique (CAT), we embed two data bits in the same size of the block via the proposed enhanced CAT (ECAT) method. The resultant payload provided by ECAT is nearly twice as large as that provided by the CAT scheme. In addition, if ECAT equipped with the least significant bit (LSB) substitution, then a large number of bits can be hidden in the ECG hosts while the resulting perceived quality is good. Simulations revealed that both the average payload and SNR and the proposed method are superior to those of the CAT-based schemes and existed ECG steganographic methods. The application of our method can be found in portable (or wearable) measurement devices.